The Effectiveness of Drama Script toward Student’s Speaking Performance in SMPI Sabilurrosyad Malang - febi akbar rizki (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2020)
Abstract: Speaking is considered as a crucial skill, because it is one of basic keys of communication. Learning speaking skill involves communicative performance and other important elements such as pronunciation, intonation, grammar, vocabulary, etc. The students of Junior High School think that speak English language is difficult to learn and complicate in expressing their ideas in English. They still look hesitate, afraid and nervous to interact with others when they are communication using English. Applying a technique that provides communicative activities and gives best situation will encourage student to have speaking practice more. Drama is a specific action to make the learning process more interesting, active and communicative. The design of the study was pre-experimental one group pre-test and post-test. For the subjects of the study, the researcher took one group or class randomly which consisted of 30 students (N=30) out of seventh grade in SMPI Sabilurrosyad Malang. The result of the paired t-test analysis demonstrated that there was significant difference in speaking ability. The students who have been taught using drama script get score higher than before. Key words: Speaking, Drama, Learning Process.